A new subspecies of Ovalona setulosa (Megard, 1967) (Cladocera: Anomopoda: Chydoridae) from the Caribbean coast of Colombia - Sinev, Artem Y.; Fuentes-Reinés, Juan M. (Zootaxa, 2016)
A new subspecies of Ovalona setulosa (Megard, 1967) (Cladocera: Anomopoda: Chydoridae) is described based on material from Laguna Navío Quebrado (La Guajira Department), Colombia. Ovalona setulosa arangureni ssp. nov. differs from the nominative subspecies in: (1) major head pores position on head shield; (2) posterior margin of labral keel without clusters of short setules; (3) more elongated postabdomen, with length/height ratio about 2.7-3; (4) male postabdomen with straight dorsal margin in whole distal portion. In outer morphology and morphology of postabdomen, O. setulosa arangureni ssp. nov. can be confused with O. glabra (Sars, 1901), but, like nominative subspecies, differs from it by interrupted connection between major head pores. Our data suggest that diversity of Aloninae species with limited distribution areas in South America is underestimated yet, and areas north and south of Amazon basin can have different local species.